Nutritional Approach of Neonatal with High Output Stoma Due to Long Segment Hirschsprung Disease: A Case Report - Aris Primadi; Filla Reviyani Suryaningrat (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: High Output Stoma (HOS) continues to be one of the most challenging problems for pediatrician especially in neonates. One of the most common causes in neonatal HOS is post resection long segment Hirschsprung disease. Case: We reported a case of three-day-old baby boy diagnosed as Hirschsprung diseases with peritonitis possibility and did laparotomy with ileal resection, double barrel ileostomy and biopsy. Nutritional management is a major subject on taking care of this type of neonatal patient. We share our experience in limited facilities with all the patient uniqueness Discussion: Loss of a significant length of the small bowel results in interrelated physiologic events as a result of decreased small intestinal mucosal absorptive cell. This leads to a lesser fraction of ingested food and intestinal secretion thus causing an excessive volume loss. The introduction of early enteral feeds promotes intestinal adaptation, with subsequent weaning off parenteral nutrition. Most off patient with high output stoma will require parenteral nutrition which is associated with acute and long-term complications. In our case, we did early nutritional intervention using parenteral and enteral nutrition, counting ongoing fluid loss trough stoma and adjust it to total daily fluid requirement. We found weight loss during hospitalized due to HOS, and we do catch up at the end. We found difficulties to adjust comparation between enteral and parenteral intake to maintain the weight gain. Conclusion: Although parenteral nutrition is often necessary, at least initially, the therapeutic goal should be to enhance intestinal adaptation and enteral nutrient assimilation, and thereby reduce parenteral nutrition requirements. Daily monitoring for ongoing fluid loss very crucial for adjusting nutrition.